Taking a mixed-methods approach to collision investigation: AcciMap, STAMP-CAST and PCM. (April 2022) - Hamim, Omar Faruqe; Hasanat-E-Rabbi, Shahnewaz; Debnath, Mithun; Hoque, Md Shamsul; McIlroy, Rich C.; Plant, Katherine L.; Stanton, Neville A.
Abstract: Recently, ergonomics and safety researchers have turned their attention towards applying combinations of sociotechnical methods rather than using single methods in isolation. In the current research, a mixed-method approach combining two systems-based methods, Accimaps and the Systems Theoretic Accident Model and Process - Causal Analysis using Systems Theory (STAMP-CAST), and one cognitive approach, the Perceptual Cycle Model (PCM), were employed in analysing a rail-level crossing incident in Bangladesh. Each method was applied individually to investigate the collision, and interventions were proposed corresponding to incident events at different risk management framework levels. The three methods provided different perspectives of the whole picture, together identifying an array of contributory factors. The complementary nature of these methods aided in proposing a comprehensive set of safety recommendations, thereby demonstrating the benefit of a mixed-method approach for collision investigation in low-income settings. Highlights: Combining systems-based and cognitive methods for road-rail collision investigation. Interventions are proposed corresponding to events at different system levels. Complementary nature of methods used brings benefits in collision investigation.